2022
DOI: 10.1002/pc.26840
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the properties of PA6/PA610 blends and glass fiber reinforced PA6/PA610 composites

Abstract: Polyamide (PA) is the mostwidely used type of semi‐crystalline polymer among engineering plastics, with its low density and high mechanical properties. But the high moisture absorption of PA6 limits its use in some areas. Blending and the addition of reinforcement can decrease the moisture absorption value of PA6. In this research, the PA6/PA610 blends and glass fiber (GF) reinforced PA6/PA610 composites were fabricated, and the features of these blends‐composites were examined. The blends and composites were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…16 In a recent study, Artykbaeva et al used a PA6-PA6,10 blend matrix with 40% GF reinforcement to improve the tensile modulus and strength by 5 times and 57%, respectively. 17 Similarly, Nikiforov et al investigated the effect of several fiber reinforcements in PA10,10 and reported that, at 40% GF loading, tensile modulus and yield strength improved by 455% and 184%, respectively. 18 In another study, Quiles-Carrillo et al reported the effects of silane treatment on the wastederived slate fiber-reinforced PA10,10 composite parts and concluded that glycidyl-silane treated fibers improved tensile modulus by 241% while the tensile strength improved by 96%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In a recent study, Artykbaeva et al used a PA6-PA6,10 blend matrix with 40% GF reinforcement to improve the tensile modulus and strength by 5 times and 57%, respectively. 17 Similarly, Nikiforov et al investigated the effect of several fiber reinforcements in PA10,10 and reported that, at 40% GF loading, tensile modulus and yield strength improved by 455% and 184%, respectively. 18 In another study, Quiles-Carrillo et al reported the effects of silane treatment on the wastederived slate fiber-reinforced PA10,10 composite parts and concluded that glycidyl-silane treated fibers improved tensile modulus by 241% while the tensile strength improved by 96%.…”
Section: Introductionmentioning
confidence: 99%
“…In one of the studies, Kuciel et al utilized flax fibers (FFs), glass fibers (GF), and carbon fibers (CF) at 10% loadings to fabricate bio‐based PA composites with 107%, 488%, and 1042% increased tensile moduli, respectively 16 . In a recent study, Artykbaeva et al used a PA6‐PA6,10 blend matrix with 40% GF reinforcement to improve the tensile modulus and strength by 5 times and 57%, respectively 17 . Similarly, Nikiforov et al investigated the effect of several fiber reinforcements in PA10,10 and reported that, at 40% GF loading, tensile modulus and yield strength improved by 455% and 184%, respectively 18 .…”
Section: Introductionmentioning
confidence: 99%
“…PA6 is widely used as a matrix for composite materials because it is a semi-crystalline thermoplastic, which has high hardness, impact resistance, excellent chemical properties, and heat resistance. [30][31][32] In addition, glass fiber (GF) and glass beads (GBs) are well-suitable as reinforced materials for composite materials because they are low density, excellent chemical and thermal stability. 33 In this paper, the synergistic reinforcement effect between particles and fibers is demonstrated by continuous GF with GBs co-reinforced nylon 6 (GB-GF/PA6) composites.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber-reinforced polymer (FRP) composites have been widely used in various fields such as transportation, energy infrastructure, and wind power generation due to their excellent specific strength and stiffness. [1][2][3][4][5] Fiber fabrics, characterized by their bidirectional structure, provide dual support for polymer matrices and exhibit excellent mechanical properties compared to unidirectional fibers. 6 The main focus of fiber-reinforced composites is to achieve good interfacial bonding, as it plays a crucial role in determining the mechanical properties of composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber‐reinforced polymer (FRP) composites have been widely used in various fields such as transportation, energy infrastructure, and wind power generation due to their excellent specific strength and stiffness 1–5 . Fiber fabrics, characterized by their bidirectional structure, provide dual support for polymer matrices and exhibit excellent mechanical properties compared to unidirectional fibers 6…”
Section: Introductionmentioning
confidence: 99%